Sistem Orientasi Tegangan Pada Chasis Aisi 4130 Gokart Phev Platform Baterai–Solar Panel - Weriono, Weriono; Siregar, Ahmad Marabdi (Rekayasa Material, Manufaktur dan Energi, 2023)
Electric car consists of a chassis that carries the vehicle's load, such as an electric motor to drive the wheels, and a battery as an energy source for the electric motor. Overall vehicle performance is controlled and monitored by the battery and engine controller systems. The objectives of the research on Design and Analysis of Electric Car Chassis Using the Finite Element Method Using Solidworks 2017 can be described as follows: Identifying aspects of the design strength of the AISI 4130 frame (hollow steel 40 x 60 mm). The design determines the wheel alignment of the wheel geometry, the angle of inclination of this wheel will later be used as a reference when making the frame and continues to make the geometry for the wheels and the width of the rear wheel tread. This axle uses a vehicle equivalent axle. Measurement, the rear wheel track of the vehicle axle is 1126 mm, and the front wheel track uses a track with a different width. For easier handling during maneuvers, the wheelbase is fixed at 1835.5mm, so the front front wheel track is wider than the rear wheel track. Mesh on the chassis using tetrahedral as shown in figure 2.a then loading is given to the node point position where the driver is on the chassis supporting the driver's load is 750 N and the battery is added, the weight of the BLDC motor and solar panel is 310 N and the maneuver is 100 N. The simulation results show the voltage value VonMises Stress with AISI 4130 material with a maximum stress value of 2.796 x 108 Pa, right maneuver 3.92 x 108 Pa and left maneuver 4.071 x 108 Pa with a given load of 1060 N. The maximum vonmises stress occurs when the kart maneuvers left while the highest maximum displacement occurs only due to the influence of gravity without being affected by vehicle maneuvers so that maneuvers can reduce displacement.